Preventing migration with vocational education? Understanding the migration - vocational education nexus - Margarita Langthaler; Dilara Gündüz (Austrian Foundation for Development Research (ÖFSE), 2020)
In many parts of the world, migration has become a controversially debated issue and a policy priority. Indeed, also development policies are increasingly including efforts to prevent migration with foreign aid. Education and TVET (Technical and Vocational Education and Training) are a part of the toolkit. Yet, while political attention is high, research on the potential role of education and TVET in mitigating migration pressure is scarce. Existing findings suggest that higher levels of education might be among the major drivers for emigration rather than the opposite.
Keywords: 330; international migration; TVET; education; development